PEMANFAATAN DIGITAL DASHBOARD RUMAH SAKIT DALAM PENGAMBILAN KEPUTUSAN DAN PENENTUAN STRATEGI DI RUMAH SAKIT ANUGERAH KOTA PEKALONGAN - Bonis Edi Artoko Edi; Lutfan Lazuardi (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2022)
Background: In realizing a complete service, accurate and fast information is needed to produce strategic decisions. The dashboardis a product of technology, which is one of the tools for providing information for hospital management. The dashboard can present theinformation needed by the user in the form of visualization on a screen so that the director can read and understand the information provided easily. Objectives: This study aimed to describe the utilization of the Hospital Digital Dashboard in decision-making and strategy determination at Anugerah Hospital Pekalongan City and the obstacles of management.Methods: The study used a descriptive design with a qualitative approach. The research samples were employees of Pekalongan CityAnugerah Hospital consisting. The research instrument used an interview guideline, voice recorder, and note taker. Data analysis usedinteractive model analysis. Results: The hospital executive information system makes it easier for executives to obtain information on all medical service activities such as Outpatient, Inpatient, Emergency Installation, and Medical Support to support decision-making for hospital executives. Digital Dashboard is a panel display created with computer software to display easy-to-read information. Digital Dashboard is a solution to meet the needs of accurate and fast data in an attractive visualization package Conclusion: The Digital Dashboard at Anugerah Pekalongan Hospital needs to be utilized optimally by making supporting tools in the form of policies and SOPs for implementers to improve the Hospital database so that later it can be processed and presented in the form of a Digital Dashboard